Slang Abbreviation in Japanese and Indonesian Written Language: Origins, Process, Similarities, and Differences - Shabella Widyastuti; Nuria Haristiani (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
Slang is one of the language styles used by young people, which is called Wakamono Kotoba in Japanese and Bahasa Gaul in Indonesian. One similar characteristic in wakamono kotoba (Japanese slang) and Bahasa Gaul (Indonesian’s slang) is the abbreviation. This research aims to compare Japanese and Indonesian slang abbreviations by explaining their origins, processes, differences, and similarities. This study was collected based on written language from Pergikuliner and Taberogu sites from March until April 2023, each taking a maximum of 50 reviews per restaurant. The review was gathered from 10 restaurants each from Indonesian and Japanese sites, meaning there are 500 data from each site and 1000 reviews from both websites. Then, the author conducted the research by analyzing the abbreviation process with similarities and differences between the two languages. The results show 398 data on slang abbreviations in wakamono kotoba and 244 data on slang abbreviations in bahasa gaul. The abbreviation process in the Japanese language mainly happens with the abbreviation of sentences or phrases, following that is an abbreviation at the end of the word, the abbreviation of two or more moras, omissions at the end of each term, the abbreviation of three words in a sentence or phrases, and abbreviations formed from initial letters of each word. On the other hand, the abbreviation process in the Indonesian language mainly happens as an omission of the word’s part, followed by shortened words from a combination of letters, acronyms of letters, combining from two separate forms, and abbreviation as letter symbols. The similarity between the two languages is used identical types of abbreviations (acronyms and toujigo), have the abbreviation process from another language, and have the same pattern in the abbreviation of the end of words. While the differences are from letters or syllables, the objects that went through the abbreviation process, changed in form in the Japanese source and tended to use foreign languages in the Indonesian source.